Crosslinking assay to study a specific cargo-coat interaction through a transmembrane receptor in the secretory pathway - Manzano-Lopez, Javier; Rodriguez-Gallardo, Sofia; Sabido-Bozo, Susana; Cortes-Gomez, Alejandro; Perez-Linero, Ana Maria; Lucena, Rafael; Cordones-Romero, Antonio; Lopez, Sergio; Aguilera-Romero, Auxiliadora; Muñiz, Manuel (PloS one, 2022)
Intracellular trafficking through the secretory organelles depends on transient interactions between cargo proteins and transport machinery. Cytosolic coat protein complexes capture specific luminal cargo proteins for incorporation into transport vesicles by interacting with them indirectly through a transmembrane adaptor or cargo receptor. Due to their transient nature, it is difficult to study these specific ternary protein interactions just using conventional native co-immunoprecipitation. To overcome this technical challenge, we have applied a crosslinking assay to stabilize the transient and/or weak protein interactions. Here, we describe a protocol of protein crosslinking and co-immunoprecipitation, which was employed to prove the indirect interaction in the endoplasmic reticulum of a luminal secretory protein with a selective subunit of the cytosolic COPII coat through a specific transmembrane cargo receptor. This method can be extended to address other transient ternary interactions between cytosolic proteins and luminal or extracellular proteins through a transmembrane receptor within the endomembrane system.